2020
DOI: 10.3389/fpls.2020.01095
|View full text |Cite
|
Sign up to set email alerts
|

Day Temperature Has a Stronger Effect Than Night Temperature on Anthocyanin and Flavonol Accumulation in ‘Merlot’ (Vitis vinifera L.) Grapes During Ripening

Abstract: Flavonoids impart color and mouthfeel to grapes and wine and are very sensitive to environmental conditions. Growth chamber experiments were performed to investigate the effect of temperature regimes and the differences between day/night temperatures on anthocyanins and flavonols in Merlot grapes. Among the regimes tested, the ones with diurnal 20°C determined the highest levels of anthocyanins and flavonols. Higher diurnal temperatures decreased those levels but increased the proportion of methoxylated and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 68 publications
11
29
0
Order By: Relevance
“…We found that the coolest region, KE, had an increase in di-substituted but a decrease in tri-substituted flavonols when compared to OO and NP ( Figure 7B). Our data is consistent with our recent study of Merlot berries that demonstrated similar effects of di-versus tri-substituted flavonols when low temperatures were compared to high temperatures (Yan et al, 2020). Moreover, Pastore et al (2017) reported a higher proportion of di-substituted flavonols with increased light exposure of berries.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that the coolest region, KE, had an increase in di-substituted but a decrease in tri-substituted flavonols when compared to OO and NP ( Figure 7B). Our data is consistent with our recent study of Merlot berries that demonstrated similar effects of di-versus tri-substituted flavonols when low temperatures were compared to high temperatures (Yan et al, 2020). Moreover, Pastore et al (2017) reported a higher proportion of di-substituted flavonols with increased light exposure of berries.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that temperature variation and water availability have little or inconsistent effects on flavonol accumulation (Price et al, 1995;Spayd et al, 2002;Downey et al, 2004;Azuma et al, 2012). However, a recent study from our group indicates that, as for anthocyanins, high temperatures (i.e., 30-35 • C) impair flavonol accumulation in the berry which is consistent with our observations here that the lowest level of flavonols is in OO, the warmest region (Yan et al, 2020). Studies have shown that sunlight intensity, and particularly the intensity of UV light, positively correlates with flavonol levels in grapes (Price et al, 1995;Spayd et al, 2002;Azuma et al, 2012;Martinez-Luscher et al, 2014a,b;Del-Castillo-Alonso et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, there is unambiguous scientific evidence that shows deleterious effects of high temperature on anthocyanin levels in the grape berry. This was reported in early studies (Buttrose et al, 1971 ; Kliewer and Torres, 1972 ; Spayd et al, 2002 ) and more recently confirmed by physiological and molecular studies (Mori et al, 2005 , 2007 ; Yamane et al, 2006 ; Azuma et al, 2012 ; Carbonell-Bejerano et al, 2013 ; Rienth et al, 2014b ; Lecourieux et al, 2017 ; Pastore et al, 2017 ; Torres et al, 2017 ; Yan et al, 2020 ). Heat stress has been shown to repress major anthocyanin biosynthesis regulators such as VviMYBA1 and downstream genes such as VviUFGT, VviCHI, VviF3H2, VviDFR , and VviLDOX .…”
Section: Temperaturementioning
confidence: 87%
“…In Kyoho grapes, temperature increases from 27 to 30°C during ripening induced a strong decrease of the transcript levels of anthocyanin genes, leading to less berry color (Shinomiya et al, 2015 ). In Merlot, an increase of day temperature of 5°C during ripening, from 20 to 25°C, resulted in a anthocyanin decrease of 37% (Yan et al, 2020 ). Besides the repression of anthocyanin related genes, high temperature may promote anthocyanin degradation, possibly via the increased activity of peroxidases (Mori et al, 2007 ).…”
Section: Temperaturementioning
confidence: 99%